"حق المستهلك الإلكتروني في العدول على ضوء التشريعات المقارنة " - أحمد, بالعبيدي رافع (جامعة الوادي University of Eloued, 2019)
" أحدثت الشبكة العنكبوتية ثورة تكنولوجية هائلة في مجال التواصل والتعاقد بين الأشخاص ويعد عقد الاستهلاك المبرم الكترونيا بين أهم العقود التي تعرف انتشارا سريعا في الوقت الراهن، كما أنه يعد من أخطر المعاملات التعاقدية المعاصرة نظرا لتزايد إبرامه بطرق ووسائل حديثة يجهل المستهلك تبعاتها، الأمر الطي اقتضى البحث عن وسائل حمائية تتناسب مع هذه الآلية التعاقدية المستحدثة، كان لزاما على التشريعات القانونية أن تتصدى وتحمي المستهلك في المعاملات الالكترونية، وتعمل على استحداث الميكانيزمات اللازمة لإعادة التوازن إلى العلاقات الاستهلاكية بما يرفع الخطر والضرر عن المستهلك، ومن بين تلك الآليات حق العدول الذي له دور كبير في الحماية من كل تسرع أو تهور أثناء إبرام أي عقد استهلاكي الكتروني" The internet has revolutionized telecommunication and remote contracting between people. The consumption contract concluded online is one of the most important contracts which is rapidly expanding in the meaning, while it is one of the most serious contemporary contractual transaction as it increasingly contracted using new means whose consequences are ignored by the consumers; which requires the search for protectionist measures in the line witch this new contractual mechanism. Thus, the legislation has to deal with the online transactions and protect the consumer from their risks, by creating the necessary mechanisms to restore balance to consumer relation in order to keep the consumer safe from all risks and harms, Among these mechanisms, there is the " Right to Retract" which has a significant role to play in protecting against any impetuosity or recklessness when entering into an electronic consumer contract.
ماستر اعمال
Keywords: العقد الالكتروني، الحق في العدول، حماية المستهلك، التعاقد بواسطة الانترنت، العلاقة التعاقدية الاستهلاكية; electronique, contract, right to retract, consumer protection, online contracting, contractual consumer relation.